Effect of Tempe Yeast Concentration and Fermentation Time on the Functional Characteristics of Fermented Peanut Flour - Martina, Salma; Erminawati, Erminawati; Naufalin, Rifda (Indonesian Journal of Food Technology, 2022)
Peanuts are one type of nuts that are quite a lot in Indonesia. Peanuts processing in Indonesia is still very limited. It is necessary to diversify the processing of peanuts into other food products. One of the efforts to diversify the peanuts process is to process them into flour. Peanuts have a weakness, namely, peanuts contain compounds of anti-nutritional substances which are mostly dominated by phytic acid and the presence of an unpleasant odor. This weakness can be overcome by the fermentation process. tempe is one of the processed products fermented in beans. The purpose of this study was to determine the functional characteristics of fermented peanut flour with variation in yeast concentration and fermentation time; and the best combination of the treatments. This study used a completely randomized design (CRD). The factors tested were the concentration of tempe yeast (3, 5 and 7%) and length of fermentation (24, 28, 32 dan 36 hours). The result of the study showed that all treatments had a significant effect on the functional characteristics of fermented peanut flour. The result shows that fermentation treatment with variations used increase the levels of water absorption capacity, solubility in water, total phenol, and antioxidant activity; but decrease the levels of oil absorption capacity and emulsion capacity. Fermented peanut flour with the best functional properties was obtained at 7% yeast concentration and 36 hours of fermentation (R3F4) treatments.